Desmin Reorganization by Stimuli Inducing Oxidative Stress and Electrophiles: Role of Its Single Cysteine Residue - Diego Moneo-Corcuera; Álvaro Viedma-Poyatos; Konstantinos Stamatakis; Dolores Pérez-Sala (MDPI AG, 2023)
The type III intermediate filament proteins vimentin and GFAP are modulated by oxidants and electrophiles, mainly through perturbation of their single cysteine residues. Desmin, the type III intermediate filament protein specific to muscle cells, is critical for muscle homeostasis, playing a key role in sarcomere organization and mitochondrial function. Here, we have studied the impact of oxidants and cysteine-reactive agents on desmin behavior. Our results show that several reactive species and drugs induce covalent modifications of desmin in vitro, of which its single cysteine residue, C333, is an important target. Moreover, stimuli eliciting oxidative stress or lipoxidation, including H2O2, 15-deoxy-prostaglandin J2, and CoCl2-elicited chemical hypoxia, provoke desmin disorganization in H9c2 rat cardiomyoblasts transfected with wild-type desmin, which is partially attenuated in cells expressing a C333S mutant. Notably, in cells lacking other cytoplasmic intermediate filaments, network formation by desmin C333S appears less efficient than that of desmin wt, especially when these proteins are expressed as fluorescent fusion constructs. Nevertheless, in these cells, the desmin C333S organization is also protected from disruption by oxidants. Taken together, our results indicate that desmin is a target for oxidative and electrophilic stress, which elicit desmin remodeling conditioned by the presence of its single cysteine residue.